Gender Moderates Results of a Randomized Clinical Trial for the Khanya Intervention for Substance Use and ART Adherence in HIV Care in South Africa - Belus, J.M.; Joska, J.A.; Bronsteyn, Y.; Rose, A.L.; Andersen, L.S.; Regenauer, K.S.; Myers-Franchi, Bronwyn; Hahn, J.A.; Orrell, C.; Safren, S.A.; Magidson, J.F. (SPRINGER/PLENUM PUBLISHERS, 2022)
Little is known about gender effects of alcohol and drug use (AOD) among people living with HIV (PLWH) in resource-limited settings. Using multilevel models, we tested whether gender moderated the effect of Khanya, a cognitive-behavioral therapy-based intervention addressing antiretroviral (ART) adherence and AOD reduction. We enrolled 61 participants from HIV care and examined outcomes at 3- and 6-months compared to enhanced treatment as usual (ETAU). Gender significantly moderated the effect of Khanya on ART adherence (measured using electronically-monitored and biomarker-confirmed adherence), such that women in Khanya had significantly lower ART adherence compared to men in Khanya; no gender differences were found for AOD outcomes. Exploratory trajectory analyses showed men in Khanya and both genders in ETAU had significant reductions in at least one AOD outcome; women in Khanya did not. More research is needed to understand whether a gender lens can support behavioral interventions for PLWH with AOD. Trial registry ClinicalTrials.gov identifier: NCT03529409. Trial registered on May 18, 2018.